Thermal, photoresponsive and conducting properties of polyoxyazobenzene hexylmethacrylate homopolymers and terpolymers: article - Majok, Abdusalam; Mohd Alauddin, Sakinah (2019)
The liquid crystal polymer in this study, Polyoxyazobenzene hexylmethacrylate homopolymers and terpolymers were characterized by using the DSC, TGA UV–visible spectrophotometry and EIS. The polymers can be used in wide range of temperature and they showed low Tg value which is under 60°C and the terpolymers is said to be in smectic phase at 148°C. Thus, polymer is said to be thermally stable. Photoresponsive properties shown clearly as both polymers performed thermal relaxation under same duration in range of 24 to 48 hours. Lastly, the terpolymers showed highest conducting properties at 110°C with dc conductivity measured, 1.69x10e-¹¹ S/cm which comparable with other studies.